Simplified Analytical Method for Predicting the Lateral Ground Displacements due to Shield Tunnelling - Lianwei Sun; Zhong-chao Li; Rong-zhu Liang (Advances in Civil Engineering)
Earth pressure balance or slurry shield tunnelling will squeeze the subsoils and lead to lateral outward ground displacement. However, current methods to estimate the shield tunnelling-induced ground displacements generally use the methods based on the face unsupported tunnelling (e.g., New Austrian tunnelling and open shield excavation), which cannot predict the lateral ground movement due to shield tunnelling. In this paper, a novel simplified analytical method is proposed to predict the ground lateral displacement during the shield advancing process. The key shield tunnelling operation factors, including the additional pressure of cutter head, the friction forces around shield body, the back-fill grouting pressure, and the soil volume loss are all considered. The lateral ground displacements induced by the four former factors are calculated by using Mindlin’s solutions. The soil volume loss-induced lateral ground displacement is calculated by employing the expression introduced by Pinto and Whittle. Combining with the displacement obtained from all the factors, the analytical method for lateral ground displacement induced by shield tunnelling is obtained. The applicability of the proposed analytical approach is verified with three well-documented case histories involving slurry shield and EPB shield machines.